PRODUCCION DE UNA REVISTA DIGITAL COMO MEDIO DE INFORMACIÓN PARA EL IMPULSO DE LOS EMPRENDIMIENTOS DE LA RUTA DEL RIO DEL CANTÓN QUEVEDO AÑO 2022. - Ramírez Diaz, Rufita Francisca (2022)
The present research work was carried out in the Quevedo canton and was born from the purpose of knowing how the media help in the promotion of the ventures of the river route. The methodology that will be used in the present research work has the purpose of obtaining information in a macro way and especially in a specific way to demonstrate the methodological development of the titling work starting from the problematic situation from its variables that are the production of a digital magazine such as means of information for the promotion of the undertakings of the river route of the Quevedo canton year 2022. To determine the stated objective, a survey was developed which was applied to the owners and administrators of the undertakings of the River Route of the Quevedo canton and thus it was possible to identify the possible reasons that cause the lack of undertakings in the river route.